FATIGUE EVALUATION OF ELECTRIC SHOVEL HANDLE WELDED STRUCTURE BASED ON BATTLLE STRUCTURAL STRESS APPROACH - ZOU Wei; CHENG ShuPei; XIAO Zheng (Jixie qiangdu)
To calculate the fatigue strength of complex handle welded structure under cyclic loading,the stress time history of handle component under cyclic loading was solved using transient modal dynamic analysis method,and the fatigue life of welded structure was calculated using mesh-size insensitive Battlle structural stress approach.It was found that the fatigue strength of original handle welded structure is insufficient because the ear plate connection structure is inconsistent,which results in stress concentration.The transition plate was added to the improved welded structure and the calculation result shows the maximum structural stress near the weld lines is 44.9% lower than that of the original structure,and the stress is relatively uniform.The fatigue life of the improved one was estimated to be 4 years and 5 months.The weld failure of improved welded structure has not occurred for more than 3 years in service in two equipments,which meets the application requirements.For large welded structures which are difficult to conduct physical tests,the numerical calculation based on Battlle structural stress approach can provide a basis for structural design.